The Phenomenon of Law Enforcement Ignoring Justice in Various Viral Cases on Social Media in Indonesia - Agustien Cherly Wereh; Marven A. Kasenda; Engeli Lumaing; Meiske Lasut; Romi Mesra (Labor Program Studi Pendidikan Sosiologi, 2024)
This study aims to investigate the phenomenon of law enforcement apparently disregarding justice in viral social media cases in Indonesia, exploring its causes, manifestations, and implications for the country's legal system and society. The research employed a qualitative methodology, combining in-depth interviews with key stakeholders, focus group discussions, social media content analysis, and a comprehensive literature review. The findings reveal a complex interplay of factors contributing to this phenomenon, including a significant disconnect between public expectations and law enforcement realities, the influence of political connections on case handling, and the emergence of digital vigilantism. The study also identified gaps in existing legal frameworks, a lack of digital literacy among both the public and law enforcement officials, and the psychological toll on officers facing public pressure. These results highlight the need for multifaceted reforms in law enforcement practices, legal structures, and public communication strategies to address the challenges posed by viral social media cases and maintain public trust in the justice system.